If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 15x + -8 + 3 = -2x + 3 + -8 Reorder the terms: -8 + 3 + 10x + 15x = -2x + 3 + -8 Combine like terms: -8 + 3 = -5 -5 + 10x + 15x = -2x + 3 + -8 Combine like terms: 10x + 15x = 25x -5 + 25x = -2x + 3 + -8 Reorder the terms: -5 + 25x = 3 + -8 + -2x Combine like terms: 3 + -8 = -5 -5 + 25x = -5 + -2x Add '5' to each side of the equation. -5 + 5 + 25x = -5 + 5 + -2x Combine like terms: -5 + 5 = 0 0 + 25x = -5 + 5 + -2x 25x = -5 + 5 + -2x Combine like terms: -5 + 5 = 0 25x = 0 + -2x 25x = -2x Solving 25x = -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 25x + 2x = -2x + 2x Combine like terms: 25x + 2x = 27x 27x = -2x + 2x Combine like terms: -2x + 2x = 0 27x = 0 Divide each side by '27'. x = 0 Simplifying x = 0
| 7p-8=-3p+6 | | 2=4y-2y-6 | | 6e-15=15 | | x+37=3x+9 | | (x-8)+23-4=36 | | 42=28-3c | | 5k+26=1 | | -3e^1-x=11 | | (-r^2)+4(-r)-4=-8 | | 6-c=3 | | 7/8x-1/3y=3 | | 7x-6.4-0.1x+3.7x-1= | | q^2-8q+20=0 | | q^2-81+20=0 | | X-4x=-6-3 | | X^2-x+5=41 | | X^2-x+5=3 | | sn=n^2 | | -30.07/-0.02 | | x^2+2xy+y^2-y= | | x^2+2xy+y^2-y=0 | | 6x^2+9=12 | | 0.26-0.02(x+2)=-0.04(2-x) | | 2z/10-9=-8 | | 26-12=2(x-3) | | 10p+13=4p-5 | | 13/6z=-9 | | (D^4+D^3-4D)y=0 | | F=r(C-z) | | 2*w+30=60-w | | X/4.6=3.5 | | 14b=-15+11z |